The motif of the king, cursed by the fairy and the sparrow-hawk: A comparative analysis - Bejanyan, Kristine H. (Имагология и компаративистика)
The article focuses on European medieval travelogues. The plot about the cursed king and the sparrow-hawk first appeared in The Travels by John Mandeville, who, judging by the date of his work, could imply Levon V. Lusignan. The plot was borrowed from Mandeville by Johannes Schiltberger, who supplemented it with a description of the location where the legend took place. As for Jean d'Arras's prose romance Mélusine, it was written in 1387 at the behest of Jean of Berry and his sister Marie of France, after Levon V had arrived in France in 1383. Successfully woven by d'Arras and later by Couldrette into the history of the House of Lusignan, the legend turned out to be strikingly consonant with the historical and political situation in the Cilician Armenia. The fairy's curse that fell upon the King of Armenia was timed by the writers to the fate of Cilician Armenia and its last king, Levon V Lusignan.